Sistem pendingin gedung 15.5 MWh dengan ice slurry CTES dan solar PV - Pamitran, Agus Sunjarianto; Azis, Rizqi Rizaldi; Mulyono, Eko; Yatim, Ardiyansyah; Lubis, Arnas (BKS-TM Indonesia, 2025)
Given the increasing concerns about the environmental impact of fossil fuel-based electricity sources, effective efforts are needed to encourage the use of green energy to meet electricity needs, especially for buildings. Air conditioning systems generally contribute the largest electricity consumption in commercial buildings, so planning an energy conservation system is very important. This study designs a building air conditioning system that uses solar power plants (PLTS) as a power source, by applying the principles of district cooling and cold thermal energy storage (CTS) with ice slurry to optimize the performance of the cooling system. With a case study in a building in Jakarta, Indonesia, this study aims to determine the capacity of the PV system and CTES that can reduce energy consumption and emissions, while considering the costs involved. This study shows 3 CTES charging schemes. In this study, a comparison of several CTES charging schemes shows that the charging scheme using a hybrid power supply is the most cost-efficient option, followed by the off-grid scheme, while the conventional system is the most expensive due to the high cost of electricity. Overall, the CTES system with ice slurry is not only a technological innovation, but also a strategic step towards a more environmentally friendly and energy-efficient building system, where energy needs are balanced with the principle of long-term sustainability.